2012+2012•2013-2013•2014
Răspunsuri la întrebare
Răspuns de
4
= 2012 + 2013 ( 2012 - 2014) =
2012 + 2013 x(-2) =
2012 - 4026 =
- 2014
2012 + 2013 x(-2) =
2012 - 4026 =
- 2014
Răspuns de
2
2012 + 2012•2013 - 2013•2014 = 2012(1 + 2013) - 2013•2014 =
2012 •2014 -2013•2014 = 2014(2012 - 2013) =2014•(-1) = -2014
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Engleza,
8 ani în urmă
Limba română,
9 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă